Narnia Günlükleri “Aslan, Cadı Ve Dolap” Sinema Filminin Mitik Arketipleri Ve Anlatısal Çözümleme Yöntemiyle İncelenmesi - Ceylan, Deniz (The Turkish Online Journal of Design, Art and Communication, 2013)
Mythology reflects the common and deep memories of nations by transforming the language and cultural codes accumulated since the beginning of mankind into an invaluable collection. Written by C.S. Lewis and half a century later, brought to the cinema screen with rich visual effects, The chronicles of Narnia: the lion, the witch and the wardrobe is the first of a series of fantastic novels that bring to day mythology. Since its birth, cinema has made use of literary narratives, and with the development of technology, the visual representation of fantastic productions has taken on a remarkable state. In this context, elements pertaining to Turkish language and culture in The chronicles of Narnia: the lion, the witch and the wardrobe will be examined and the film’s characters, time and space will be evaluated.
Keywords: Narnia Günlükleri; Mitoloji; Sinema; Anlatısal Çözümleme; The Chronicles of Narnia; Mythology; Cinema; Narrative Analysis